Estrategias MIP implementadas para el control del vector del HLB y otras plagas en los LD. Producto 4 - Aguirre, Maximo Raul Alcides; Giancola, Silvana Ines; Peralta, Carmen Ofelia; Segade, Gonzalo; Carbajo Romero, Maria Soledad; Aybar, Sonia Elizabeth; Tapia, Silvia Norma; Acuña, Luis Eduardo; Badaracco, Alejandra; Acuña, Pedro; Buenahora, José; Hochmaier, Vanesa Elisabet; et al. (FONTAGRO, 2024)
As part of the implementation of the project co-financed by FONTAGRO, Sustainable control of the HLB vector in family farming, 52 reports are presented on integrated pest management (IPM) strategies implemented in 16 demonstration plots located in citrus farms of family farmers: 12 in Argentina (provinces: Buenos Aires, Entre Ríos, Corrientes, Misiones, Formosa, Tucumán, Jujuy and Catamarca), 2 in Uruguay (departments of Salto and Paysandú) and 2 in Paraguay (department of Itapúa). The information surveyed was carried out from 2019 to 2023 through systematic pest and disease monitoring, both in IPM demonstrator plots (LD) and in conventional plots under the producer's usual management (LC), with emphasis on the early detection of the HLB vector, Diaphorina citri, with 3 complementary monitoring methods (tapping, visual observation and use of yellow cards). The intervention strategies implemented were chemical (with low toxicological classes), biological and cultural. As a result of IPM, a decrease in the population of Diaphorina citri was observed in 3 of the 9 demonstration plots - where the vector was recorded - compared to conventional plots. The abundance of natural enemies of the HLB vector was 38% higher in 13 demonstration plots than in conventional plots. Systematic monitoring and the reduction in the use of broad-spectrum toxic products in favor of more environmentally friendly ones, among other IPM practices, explain the decrease in the population of pests, Diaphorina citri and others, and the notable increase in beneficial fauna.